Метафорические аппозитивные словосочетания с личным значением в тестах современной русской прессы - Murawska, Paulina (Studia Rossica Posnaniensia, 2015)
This article is devoted to studying metaphorical appositive asyndetic phrases in the language of the Russian press. The author presents a variety of aspects related to the semantic characteristics of metaphorical, appositive asyndetic phrases and aims to define the importance of these language units for sociolinguistic and psycholinguistic analysis.